A brief analysis of the circumstances of the current coal industry and its trends in China. (1st January 2015) - Liu, Xinjie; Luan, Hebing
China is the biggest coal producer and consumer in the world. Coal is the dominant fuel source in China. Coal production in China is estimated to increase and peak at 4.5 billion tons in 2030. However, coal in the energy consumption structure is expected to reduce to less than 50% in 2025. The efficient coal capacity should be three billion tons and the reasonable capacity is 3.3-5 billion tons. So the annual rate of increase should be controlled at about 3%. The security situation has been improved persistently. It is estimated that the number of accidents could be controlled less than 50 in 2016 and the casualties could be decreased to less than 500 in 2018. It is proposed that the coal distribution should be optimised and the production should be limited. The scientific, green and low–carbon energy development strategy could promote the sustainable development of coal industry.